(untitled) (GESTIÓN Y TENDENCIAS, 2019)
Various studies show that women behave more conservatively than men when investing. Psychology suggests that in the general population these differences are explained by emotions, individual confidence, and the way men and women perceive risk situations. This article analyzes whether there are gender differences in decisions relating to pension fund investments in Chile, using aggregate data from the Superintendency of Pensions. The results show no major differences in the percentage of men and women who choose their multi-funds versus those who accept the default option offered by the system. Among those who do choose their multi-funds, no major aggregate differences are observed in the risk level of those funds either.